Bibliometric Mapping of Culinary Tourism in Destination Development: Analisis Bibliometrik Pariwisata Kuliner dalam Pengembangan Destinasi Wisata - Fuada, Mifthahul; Faridah, Anni; Yulastri, Asmar; Kasmita, Kasmita; Putri, Meri Yulianti (Academia Open, 2026)
General Background: Culinary tourism has become an increasingly important component of tourism development due to its association with destination attractiveness, cultural heritage, sustainability, and visitor experiences. Specific Background: The growing body of literature on culinary tourism has expanded across tourism studies, yet the intellectual structure and thematic evolution of research linking culinary tourism and tourism destinations remain fragmented. Knowledge Gap: Previous studies have widely discussed food tourism and gastronomy; however, a focused bibliometric mapping of culinary tourism in relation to destination development during the 2015–2024 period remains limited. Aims: This study aims to map the evolution of research on culinary tourism and tourism destinations through a bibliometric analysis. Results: Data retrieved from the Scopus database yielded 47 articles from 37 journals, which were analyzed using OpenRefine, VOSviewer, and Bibliometrix. The findings reveal a substantial increase in publication activity after 2020, reaching its highest level in 2023. Dominant themes include tourist destinations, tourism, tourist behavior, sustainability, ecotourism, tourism development, and heritage tourism. Network visualization further shows that culinary tourism occupies a central position connected to destination development, tourist motivation, and cultural heritage preservation. Novelty: This study provides a destination-focused bibliometric mapping by integrating keyword network analysis, publication trends, journal distribution, and international collaboration patterns within culinary tourism research. Implications: The findings offer a comprehensive knowledge base for researchers, practitioners, and policymakers in formulating sustainable destination development strategies and identifying future research directions in culinary tourism. HIGHLIGHTS • Publication activity on culinary tourism increased substantially after 2020 and reached its highest level in 2023. • Tourist destinations, sustainability, tourist behavior, and heritage-related themes constitute the dominant research clusters. • Culinary tourism occupies a central position linking destination development, tourist motivation, and cultural preservation. KEYWORDS Culinary Tourism; Food Tourism; Tourist Destinations; Sustainable Tourism; Destination Development